Implementasi Sistem Klasifikasi Inventaris Menggunakan Metode Clustering dengan Algoritma K-Means untuk Pengelolaan Stok Barang di D'Cafe Indramayu - Dina Rima Dhona; Yulianingsih Yulianingsih; Suranto Saputra (Faktor Exacta, 2025)
One effective marketing strategy to attract consumer interest is the implementation of a "buy one get one free" promotional program on select products. However, this strategy necessitates sustainable inventory availability and must be aligned with the marketing unit's objectives. This research applies the K-Means algorithm to classify products based on price parameters and stock availability levels. The analysis results reveal the formation of three primary clusters: (1) products within the low to medium price range, (2) products within the medium to high price range, and (3) products in the highest price category. This clustering is based on the proximity of each product to its cluster centroid, accompanied by quantitative information regarding the number of products within each cluster. The output from this analysis is implemented through an application developed using the Java programming language. This application is designed to be utilized by the marketing unit in formulating and optimizing sales strategies to increase sales volume and enhance inventory management effectiveness.